ENT300 Fundamental of Entrepreneurship. Business Plan : CoconutLicious Enterprise / Noor Syafikha Binti Bujang Hassim... [et.al] - Bujang Hassim, Noor Syafikha; Bujit, Adzrima; Jamil, Mohd Azri Hisyam; Sharkawi, Siti Hidana; Sukacha, Indrakasumi; Simon @ Irwansyah, Nur Asyikin (2015)
The name of our company is CoconutLicious Enterprise. Our business is in the form of partnership which consists of six members. We had choose this kind of business because it shows the equality and no one will be discriminated as the profits and losses are equally divided in the end of the accounting period. In other way, the partnership is a perfect option to be taken because the shareholders will always sharing ideas and knowledge in order to gain profit and achieve high productivity time to time. Each partner contributes certain amount of capital as agreed in the partnership agreement. Each of CoconutLicious partner contributes RM 1500.There are no sleeping partners and all are entitled to participate in the business management. We agreed that Noor Syafikha Binti Bujang Hassim is our General Manager, Nur Asyikin Binti Simon @ Irwansyah is the Administration Manager, Adzrima Binti Bujit and Mohd Azri Hisyam Bin Jamil are the Operation Manager, Siti Hidana Binti Sharkawi as Financial Manager and Indrakasumi Binti Sukacha as Marketing Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability. CoconutLicious Enterprise is a beverages shop that offer coconut milk shake at a cheap and affordable price with high quality materials. We have decided to only provide coconut milk shake in our menu because we want to focus only on one product. Our premise will be located at'G34&G91,The Summer Shopping Mall 1391-1403 & 108,Blk 1,Samarahan Land Dist, Jalan Dato Mohd Musa,94300 Kota Samarahan Samarahan, Sarawak. We offer two type of coconut milk shake whereby the first type is the normal one, each cup will cost RM 3.00 and the second type is the special one with vanilla ice cream as a topping, each cup will cost RM 3.50.